Dating the origin and dispersal of hepatitis B virus infection in humans and primates1. Issue 3 (7th February 2013) - Paraskevis, Dimitrios; Magiorkinis, Gkikas; Magiorkinis, Emmanouil; Ho, Simon Y.W.; Belshaw, Robert; Allain, Jean‐Pierre; Hatzakis, Angelos
Abstract The origin of hepatitis B virus (HBV) infection in humans and other primates remains largely unresolved. Understanding the origin of HBV is crucial because it provides a framework for studying the burden, and subsequently the evolution, of HBV pathogenicity with respect to changes in human population size and life expectancy. To investigate this controversy we examined the relationship between HBV phylogeny and genetic diversity of modern humans, investigated the timescale of global HBV dispersal, and tested the hypothesis of HBV‐human co‐divergence. We find that the global distribution of HBV genotypes and subgenotypes are consistent with the major prehistoric modern human migrations. We calibrate the HBV molecular clock using the divergence times of different indigenous human populations based on archaeological and genetic evidence and show that HBV jumped into humans around 33, 600 years ago; 95% higher posterior density (HPD): 22, 000‐47, 100 years ago (estimated substitution rate: 2.2 × 10−6; 95% HPD: 1.5‐3.0 × 10−6 substitutions/site/year). This coincides with the origin of modern non‐African humans. Crucially, the most pronounced increase in the HBV pandemic correlates with the global population increase over the last 5, 000 years. We also show that the non‐human HBV clades in orangutans and gibbons resulted from cross‐species transmission events from humans that occurred no earlier than 6, 100 years ago. Conclusion: Our study provides, for the first time, an estimated timescale for the HBV epidemic that closely coincides with dates of human dispersals, supporting the hypothesis that HBV has been co‐expanding and co‐migrating with human populations for the last 40, 000 years. (HEPATOLOGY 2013)